Algae of Lima ground and its surrounding area - Zúñiga A., Reina (1980)
This paper deals with the systematic study of some species of Microcoleus, Nodularia, Cylindrospermum, Botrydium, Vaucherio and Stichococcus identified on soil samples from some places of Lima city and adjacent areas.